Pre‐thermal treatment in binary solvent systems promoting β crystalline phase of electrospun poly(vinylidene fluoride) nanofibers. Issue 8 (21st April 2020) - Nuamcharoen, Praewpanit; Kobayashi, Takaomi; Potiyaraj, Pranut; Shiozaki, Makoto
Abstract: Poly(vinylidene fluoride) (PVDF) nanofibers were fabricated via electrospinning with an investigation of various ratios of binary solvents at different temperatures. The amount of acetone influenced the morphology. Scanning electron microscopy showed a PVDF membrane composed of smooth and unblemished fibers without beads and dark spots with small diameters of 201 ± 54 nm at a dimethylformamide‐to‐acetone ratio of 4:6. The temperature of pre‐thermal treatment from room temperature to 120 °C was investigated to promote the β crystalline phase in electrospun PVDF nanofibers. The result was characterized using Fourier transform infrared (FTIR) spectroscopy and X‐ray diffraction (XRD). PVDF solution prepared at 80 °C was used to increase the β crystalline phase of the electrospun PVDF nanofibers due to the transformation of α to β phase occurring during the spinning process and also bead‐free PVDF nanofibers were obtained. Differential scanning calorimetry revealed crystallization behavior corresponding with that determined using FTIR spectroscopy and XRD. Therefore, the solvent proportion and pretreatment temperature were observed to affect ultrafine nanofiber and crystalline structure of PVDF, respectively. © 2020 Society of Chemical Industry Abstract : The effect of pre‐thermal treatment in binary solvent systems on the properties of electrospun PVDF was investigated. Unblemished nanofiber morphology was observed on adding acetone. Increasing the pretreatment temperature promoted formation of β crystalline phase.